Alkylation of Phosphinite/Phosphonite-Boranes via Temporary Protection of the P–H Bond - Modzelewski, Kamil; Sowa, Sylwia (Synthesis, 2020)
A new alkylation protocol for the synthesis of tertiary phosphonite/phosphinite-boranes is developed. P-Alkylation products are obtained exclusively in moderate to very good yields from easily accessible (1-hydroxy-1-methylethyl)/(1-hydroxy-1-cyclohexyl) phosphonite/phosphinite-boranes upon reaction with a variety of electrophiles under mild conditions. The methodology opens up new synthetic routes for organophosphorus chemistry and offers access to valuable alkyl phosphonite/phosphinite-boranes. In contrast to previously reported oxidative removal–substitution sequences for the preparation of optically active phosphinite-boranes, our protocol provides a one-step procedure that occurs without loss of stereochemical information at phosphorus. This new approach provides a rather advantageous protocol when compared to direct alkylation methods (which may undergo P-epimerization) and occurs in a stereoselective manner even at 0 °C.
Keywords: alkylation; chemoselectivity; protecting group; in situ deprotection; phosphinite-boranes; phosphonite-boranes; diastereoselectivity